2010
DOI: 10.1111/j.1741-3729.2009.00582.x
|View full text |Cite
|
Sign up to set email alerts
|

“Not the Romantic, All Happy, Coochy Coo Experience”: A Qualitative Analysis of Interactions on an Irish Parenting Web Site

Abstract: Support groups in online communities provide an anonymous place to exchange information and advice. Previous research has suggested that these groups offer a safe, nonjudgmental forum for new parents to share experiences and interact anonymously. This study investigated how participants in online parenting groups experience support via the Internet and what types of support they receive. All posts made over a 2‐week period on the parenting‐related discussion boards of an Irish parenting Web site were analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
0
12

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(89 citation statements)
references
References 41 publications
(47 reference statements)
4
73
0
12
Order By: Relevance
“…Previous critical researchers of mothers' blogs and online forums for pregnant women and mothers have contended that such interactions and other site content tend to reproduce dominant notions of 'good motherhood' without offering many alternatives for women 32,33 . Pregnancy apps similarly reproduce limited concepts of female reproduction and embodiment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous critical researchers of mothers' blogs and online forums for pregnant women and mothers have contended that such interactions and other site content tend to reproduce dominant notions of 'good motherhood' without offering many alternatives for women 32,33 . Pregnancy apps similarly reproduce limited concepts of female reproduction and embodiment.…”
Section: Discussionmentioning
confidence: 99%
“…Madge and O'Connor also found that new mothers gained reassurance and strength from realizing that others had the same hurdles to overcome [17] and Brady & Guerin found the power of shared experiences in contributing to feelings of normalcy [4]. Access to the Internet and consequently a variety of web services provides the opportunity for new mothers gain strength from these shared experiences.…”
Section: Have Picked Up Loads Of Tips On Forums Just By Having a Wementioning
confidence: 99%
“…Evidence suggests that use of these sites contributed to a high general perception of support (our emphasis) [26], a greater sense of empowerment [27] and seemed to rival the support traditionally found in neighbour communities [4].…”
Section: Related Workmentioning
confidence: 99%
“…There is thus, a broader debate to be had about the words we use to refer to women's/mothers' textual practices on social media. This is reflected to an extent in the title of Brady & Guerin's (2010) work on online parenting discussions where they say these sites are 'not all romantic, all happy, coochy coo'. Rogers ' (2015) terminology of "maternal essayists"…”
Section: Mothers On Social Mediamentioning
confidence: 99%